Perancangan Aplikasi pada Pengelolaan Sewa Barang - Windya Hartasih; Denny Sagita Rusdianto; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In rental services, activity that usually do by rental provider are item ordering, item taking, item returning, item checking, and bookkeeping. Nowadays, many rental providers have difficulties for running their business activity, such as item scheduling, order recording, differences between item inventory and routine bookkeeping that causes losses and problems with customers. Moreover, the rental providers have limited infrastructure, by keep using rental note, whiteboard, and Microsoft Excel software for bookkeeping. Therefore, the rental providers need an rental management application which is independent in order to not depend on infrastructure or need more infrastructure, so that the service providers can only use smartphone without adding other infrastructure to manage rental services. This application designed using OOAD (Object Oriented Analysis and Design) method and REST web service. Designing this application include service design, architecture design, component design, data design, user interface design, and application design architecture. This design of application has been tested using Traceability Matrix, (Coupling Between Object Classes) CBO, (Response for a Class) RFC, (Lack of cohesion in methods1) LCOM1 metrics, and (Lack of cohesion in methods2) LCOM2 metrics. The result of this application design has low coupling because of the CBO's average value<=5 and RFC's average value<=100 so it have high understandability and low cohesion because of LCOM>1. The result of this application design also has high adaptability because of the CBO's average value is between 1 and 3, RFC's average value between 1 and 69, and fulfill LCOM2's value between 0 and 1. Furthermore, all artifacts are made based on the use case that was made before, because each column and row in the traceability matrix have a value of 1.